Canopy height explains species richness in the largest clade of Neotropical lianas. Issue 1 (17th September 2019) - Meyer, Leila; Diniz‐Filho, José Alexandre F.; Lohmann, Lúcia G.; Hortal, Joaquín; Barreto, Elisa; Rangel, Thiago; Kissling, W. Daniel
Abstract: Aim: Tall and structurally complex forests can provide ample habitat and niche space for climbing plants, supporting high liana species richness. We test to what extent canopy height (as a proxy of 3‐D habitat structure), climate and soil interact to determine species richness in the largest clade of Neotropical lianas. We expect that the effect of canopy height on species richness is higher for lianas from closed tropical rain forests compared to riparian and savanna habitats. Location: Neotropics. Time period: Present. Major taxa studied: Tribe Bignonieae (Bignoniaceae). Methods: We used structural equation models to evaluate direct and indirect effects of canopy height, climate (temperature, precipitation and precipitation seasonality), and soil (cation exchange capacity and soil types) on overall Bignonieae species richness (339 liana species), as well as on species richness of lianas from forest, riparian and savanna habitats, respectively. We further performed multiple regression models with Moran's eigenvector maps to account for spatial autocorrelation. Results: Canopy height was a key driver of liana species richness, in addition to climate and soil. Species richness of forest lianas showed a strong positive relationship with canopy height whereas the relationship was less pronounced for riparian species. Richness of savanna species decreased with increasing canopy height. Climate also explained a substantial proportion of variation in liana species richness whereas soil variables showed little explanatory power. Main conclusions: The relationship between canopy height and liana species richness differs among habitats. While forest and riparian lianas benefit from tall and complex habitats that provide physical support to reach the canopy to escape low light availability in the understorey, high light availability in open habitats and an increased risk of embolism of conductive vessels for lianas with long stems living in areas with high seasonality might explain the inverse relationship between species richness and canopy height in savannas.